Optimalisasi Pembelajaran Dengan Media Berbasis Android dan Metode Flipped Learning di Lembaga Bahasa - Idrus, Imriani; Nurdiana, Defi Dachlian; Rofiq, Ainur (Chalim Journal of Teaching and Learning, 2024)
The use of technology in education allows the development of innovative learning media. Android-based learning media, for example, can be integrated with the flipped learning method to increase learning effectiveness. Flipped Learning is a learning model that changes the conventional way of learning. If usually the material is taught in class and assignments are done at home, in flipped learning, students study the material independently at home and discuss or do assignments in class. whereas in the flipped learning method, the material is first provided via learning videos which students must watch at home or anywhere via smartphone devices. In contrast to conventional learning, where students tend to passively receive material, in flipped learning, students more actively participate in discussions and collaboration to complete assignments in class. The teacher acts as a facilitator who guides the learning process. The specific aim of the research is to see the effectiveness of using Android-based learning media which will be applied to the Flipped Learning learning method at the LIA Makassar Language Institute and to find out its attractiveness, convenience and usefulness. Meanwhile, the general aim of the research is to encourage the achievement of the objectives of the research strategic plan of the Bina Adinata Bulukumba Institute of Technology and Business. Implementation of Android-based learning media which includes preparation stages (readiness of teaching materials/learning materials, software and hardware), data analysis stages, testing stages and subsequent development stages. With this Android-based learning media, it is hoped that it will increase creativity and motivate students so that their learning outcomes increase and students can complete their learning on time.